EDUKASI ONLINE KETERAMPILAN PERAWATAN MANDIRI PADA PASIEN DIABETES MELLITUS DI ERA NEW NORMAL - Saftarina, Fitria; Fitri, Hilda; Tricia, Yulita; Stepriyani, Selly; Isti Anggraini, Dian (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
It is estimated that by 2045, the number of DM sufferers will reach 630 million of people. Indonesia,based on the 2018 Basic Health Survey, the prevalence of DM reached 10.9%. During the pandemicof Covid-19, people with pre-existing medical conditions such as Diabetes Mellitus (DM) were moresusceptible to becoming seriously ill due to covid-19. Health services were also hampered duringthe pandemic of Covid-19. The purpose of this activity is to increase knowledge about DM, self-careskills in patients or care-givers. Health Education was carried out through Whatsapp Group onlineeducation in the form of providing material knowledge about DM disease, self-care skills for DMpatients in the new normal era, and prevention of DM patients from Covid-19, educational videos,and flyers. This activity was attended by 168 participants. The results of the activity show thatonline education can increase knowledge about self-care skills in DM patients and care-givers. Thecontinuation of this activity was followed up through providing information on WhatsApp Groupand online consultation (telemedicine)